Information systems for monitoring and evaluation of company's value; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Zhdanova A. B. Anna Borisovna; Bannova K. A. Kristina Alekseevna; Rakhimov T. R. Timur Rustamovich; Sosnin V. N. Vladimir Nikolaevich; Kamenskaya K. Y. Kseniya Yurjevna (2016, 2016)
Title screen